Unpacking the Child Penalty Using Personnel Data: How Promotion Practices Widen the Gender Pay Gap - Yoko Okuyama; Takeshi Murooka; Shintaro Yamaguchi (Institute of Labor Economics (IZA), 2025)
We estimate the child penalty using detailed personnel records that enable decomposition into distinct pay components. Our analysis reveals that the penalty is initially driven by reductions in time-based pay following childbirth. However, job-rank-based pay becomes increasingly significant over time, emerging as the dominant factor by the 15-year mark. These effects are interconnected: reduced working hours lead to lower performance evaluations, which subsequently limit promotion opportunities. Our theoretical model demonstrates that current promotion practices, which reward extended hours at entry-level positions, can generate production ineffciency. This finding suggests that addressing promotion practices could simultaneously reduce gender inequality and improve talent allocation, making a compelling business case for organizational reform.
Keywords: J13; J16; J24; J31; M51; 330; child penalty; promotion; management practice; personnel economics; internal labor markets; gender pay gap; career progression